2021
DOI: 10.3389/fmed.2021.683900
|View full text |Cite
|
Sign up to set email alerts
|

Nailfold Capillaroscopy With USB Digital Microscopy in Connective Tissue Diseases: A Comparative Study of 245 Patients and Healthy Controls

Abstract: Background: Nailfold capillaroscopy (NFC) is a valuable tool to detect microcirculation abnormalities in connective tissue diseases (CTDs). However, whether the universal serial bus (USB) digital microscopy used as onychoscopy is as effective as the videocapillaroscopy in determining the diagnostic and prognostic values of CTDs remains to be determined.Objective: This study aims to investigate NFC features of systemic lupus erythematosus (SLE), dermatomyositis (DM), and systemic sclerosis (SSc) patients and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 60 publications
(84 reference statements)
1
11
0
Order By: Relevance
“…The (video)dermoscopic features of skin symptoms in the course of DM have not been extensively studied so far [7][8][9][10][11][12][13][14][15]. Data from the literature point at potential application of (video)dermoscopy in the assessment of nailfolds (capillaroscopy) [7][8][9][10], scalp (trichoscopy) [11,12], filiform papillae of the tongue [13], hand lesions [14], and cutaneous changes in erythrodermic DM [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The (video)dermoscopic features of skin symptoms in the course of DM have not been extensively studied so far [7][8][9][10][11][12][13][14][15]. Data from the literature point at potential application of (video)dermoscopy in the assessment of nailfolds (capillaroscopy) [7][8][9][10], scalp (trichoscopy) [11,12], filiform papillae of the tongue [13], hand lesions [14], and cutaneous changes in erythrodermic DM [15].…”
Section: Discussionmentioning
confidence: 99%
“…Capillaroscopy use has great potential in DM, and several studies confirmed the application of handheld dermatoscopes and videodermatoscopes in the assessment of nailfold capillaries [7][8][9][10]. (Video)dermoscopy enables the visualization of "bushy" capillaries, dilated capillaries, nailfold bleedings, and avascular areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13] So far, dermoscopy has been predominantly used for the assessment of nail fold capillaries and proved to be a reliable tool to detect dilated capillaries, 'bushy' capillaries, nail fold bleedings and avascular areas. [5][6][7]11 Dermoscopy has also been utilized for the visualization of filiform papillae of the tongue in connective tissue diseases. 9 Trichoscopic features of DM have also been reported in a few papers.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the complex disease etiology and our incomplete understanding of the relationship between these factors and hair loss, we presume that genetic predisposition, stress, and environmental factors affect immune activation and influence AA occurrence. [163][164][165][166][167][168][169] Further, novel targeted therapies that treat AA have been reviewed. However, a complete response without relapse remains challenging.…”
Section: Discussionmentioning
confidence: 99%